2012
DOI: 10.1029/2012gl053716
|View full text |Cite
|
Sign up to set email alerts
|

Experimental craters formed by single and multiple buried explosions and implications for volcanic craters with emphasis on maars

Abstract: .[1] Craters at many volcanoes, including most maars, are formed by multiple subsurface explosions. Experiments compared the crater formed by a single large, buried explosion, with craters formed by multiple explosions with the same cumulative energy. Explosive charges were detonated in pads composed of layered aggregates, in three configurations: (1) a single large charge buried near its optimal crater excavation depth; (2) three charges, each with 1/3 the energy of the first one, buried at approximately the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 12 publications
3
42
2
Order By: Relevance
“…For instance, Valentine and White [29] propose an alternative model that allows multiple levels of country rock disruption and fragmentation, based on effective mixing by debris jets, an important subsurface transport phenomenon in phreatomagmatic vent complexes that is defined as an upward-moving stream of volcaniclastic debris, magmatic gases, and water vapor ± liquid water droplets, occurring on multiple vertical levels within a growing subsurface diatreme (e.g., [144]). This conceptual model is in accordance with the observed irregular distribution of accidental lithics in ejecta rings (e.g., [145]), field examples on diatreme geometry (e.g., [79]), but also on experimental cratering studies (e.g., [109,124,146]) and geophysical modeling (e.g., [80,81,147]). Chako Tchamabé et al [11] also suggested that the variation of juvenile populations within the stratigraphic sequence of maars might reflect a potential mode of explosions during maar-diatreme formation (Figure 7).…”
Section: Growth Of Complex Monogenetic Volcanoessupporting
confidence: 54%
“…For instance, Valentine and White [29] propose an alternative model that allows multiple levels of country rock disruption and fragmentation, based on effective mixing by debris jets, an important subsurface transport phenomenon in phreatomagmatic vent complexes that is defined as an upward-moving stream of volcaniclastic debris, magmatic gases, and water vapor ± liquid water droplets, occurring on multiple vertical levels within a growing subsurface diatreme (e.g., [144]). This conceptual model is in accordance with the observed irregular distribution of accidental lithics in ejecta rings (e.g., [145]), field examples on diatreme geometry (e.g., [79]), but also on experimental cratering studies (e.g., [109,124,146]) and geophysical modeling (e.g., [80,81,147]). Chako Tchamabé et al [11] also suggested that the variation of juvenile populations within the stratigraphic sequence of maars might reflect a potential mode of explosions during maar-diatreme formation (Figure 7).…”
Section: Growth Of Complex Monogenetic Volcanoessupporting
confidence: 54%
“…However, to our knowledge, only Valentine et al . [] performed field‐scale explosion experiments that involved multiple explosions occurring within the same crater. The crater shapes and sizes were documented after each explosion [ Valentine et al ., ], while the sub‐crater deposits (partly analogous to natural diatremes) are investigated by Ross et al .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there are alternative processes, such as volcanic eruptions and explosions, that can also produce craters [5][6][7][8][9][10][11][12]. For instance, a maar is a natural depression created by an underground steam explosion that occurs when magma comes into contact with shallow groundwater [7].…”
mentioning
confidence: 99%